2004
DOI: 10.1159/000078438
|View full text |Cite
|
Sign up to set email alerts
|

Th1 and Th2 Serum Cytokine Profiles Characterize Patients with Hashimoto’s Thyroiditis (Th1) and Graves’ Disease (Th2)

Abstract: Objectives: The aim of this study was to document the pattern of immune response, assessed by the measurement of both Th1 and Th2 serum cytokines, in patients suffering from autoimmune thyroid disease and toxic nodular goiter. Methods: Both Th1 and Th2 serum cytokine levels were assayed in patients suffering from Graves’ disease (GD, n = 25), Hashimoto’s thyroiditis (HT, n = 21), and toxic nodular goiter (TNG, n = 7) and compared with corresponding levels of 25 healthy controls. Serum concentrations of IL-2, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
91
2
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(105 citation statements)
references
References 31 publications
5
91
2
7
Order By: Relevance
“…6 Higher levels of IFN-γ and IL-12 have been reported among patients with HT, which may account for the increased expression of T-bet in these patients. 27,28 It seems that HT is a Th1-dependent process in that the IFN-γ-secreting Th1 cells activate cytotoxic T lymphocytes and macrophages, killing thyroid follicular cells. 28 The current study also demonstrated that expression of GATA 3 , the Th2 transcription factor, was significantly increased among HT patients as compared to the healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…6 Higher levels of IFN-γ and IL-12 have been reported among patients with HT, which may account for the increased expression of T-bet in these patients. 27,28 It seems that HT is a Th1-dependent process in that the IFN-γ-secreting Th1 cells activate cytotoxic T lymphocytes and macrophages, killing thyroid follicular cells. 28 The current study also demonstrated that expression of GATA 3 , the Th2 transcription factor, was significantly increased among HT patients as compared to the healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that these two functionally opposite states can develop in the same person at different periods suggests that the Th1/Th2 balance and the related cytokine profile is a dynamic process, evolving under the influence of external factors operating in the local environment of the thyroid gland [23,24].…”
Section: Szkolenie Podyplomowementioning
confidence: 99%
“…On the basis of the cytokine secretion profile, CD4+ Th lymphocytes were originally subdivided into Th1 and Th2 cells. Th1 produce interleukin 2 (IL-2), interferon γ (IFN-γ), and lymphotoxin and induce cellular responses [3,4]. Th2 cells secrete IL-4, IL-5, IL-6, IL-9, IL-10, and IL-13 and promote production of antibodies by B lymphocytes [3,4].…”
mentioning
confidence: 99%
“…Th1 produce interleukin 2 (IL-2), interferon γ (IFN-γ), and lymphotoxin and induce cellular responses [3,4]. Th2 cells secrete IL-4, IL-5, IL-6, IL-9, IL-10, and IL-13 and promote production of antibodies by B lymphocytes [3,4]. A predominant Th1-driven autoimmune response has been clearly recognized in HT, while Graves' disease (GD) is induced by thyroid stimulating autoantibodies to TSH receptor and is considered a Th2-related disease [3,4].…”
mentioning
confidence: 99%